Incel, the Manosphere, and Toxic Masculinity: Issues Depicted in Netflix’s “Adolescence” Miniseries - Herusatoto, Hesthi (Humanis, 2025)
This article is based on library research after watching the Netflix four-episode limited series "Adolescence". By collecting information from published materials, this article attempts to provide an understanding of the words ‘incel’, ‘the manosphere’, and ‘toxic masculinity’ which become issues addressed in "Adolescence"  and to show how the issues are portrayed in the British miniseries. Socio-psychological approach is used to examine Jamie, the main character, who is given the label of an incel by Katie, his schoolmate and to examine Jamie’s father, Eddie. The findings of the library research reveal that the meaning of the word 'incel’ (involuntary celibate) has shifted from its original meaning coined in 1997. Incel in the manosphere, which is a cluster of online communities with misogynistic and toxic masculinity contents, has become negative movement against women since 2012. Jamie learns toxic masculinity from his father and the manosphere. His exposure to toxic content in the manosphere has fueled his resentment after being rejected by Katie and has triggered him to kill her.